Assessment of resistant varieties of maize against Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) in laboratory conditions - Shahid, Farooq Ahmad, Kishwar Nawaz, Muhammad; Mansoor-ul-Hasan, Muhammad Sagheer; Unsar Naeem-Ullah, Muhammad Sadique, Muhammad Asad Saleem (Journal of Scientific Agriculture, 2019)
Grains of five different maize varieties (MMRI Yellow, Pearl White, Malka-2016, YH-1898 and Sadaf) were evaluated for their comparative resistance to Tribolium castaneum under laboratory conditions (30+2°C and 70+5 R.H). Data of percent mortality were taken after 30, 60 and 90 days. Significantly, the maximum mortality of adults was observed in MMRI Yellow (28.57%, 33.67% and 41.61%) in sound seeds and lowest mortality was noted in Sadaf (14.88, 21.33% and 24.99%) during observation period. The seed germination was highest in MMRI Yellow which was 90% while lowest was noted in Sadaf as 50%. The highest protein contents were recorded in Malka-2016 (12.83% and 11.60%) and lowest in YH-1898 (3.90% and 2.50%) in both sound and cracked seeds. However, maximum fiber contents were observed in Malka-2106 (2.76% and 2.16%), while lowest (0.43% and 0.30%) in YH-1898 for both seed types. Consequently, MMRI Yellow variety was proved to be resistance as compared to other varieties with maximum germination. It can be concluded that resistant varieties of maize could be utilized in breeding program to reduce the post-harvest losses of grains.